Hospital care for postpartum women: integrative review (Research, Society and Development, 2023)
Objective: To analyze the scientific production regarding hospital care for women in the postpartum period. Methodology: Integrative literature review, which used the PICO strategy to construct the following research question: “What is the scientific production on hospital care for women in the postpartum period?”. The searches were carried out in the SciELO, LILACS and MEDLINE databases using the descriptors: Período Pós-Parto, Assistência Hospitalar, Postpartum Period, Hospital Care. After applying the established inclusion and exclusion criteria, six scientific articles were selected. For the analysis of these studies, thematic analysis was used. Results: The selected studies were carried out and published predominantly in South American countries. After reading and analyzing the content of these studies, two thematic units were constructed, namely: Postpartum hospital care: weaknesses and potential for comprehensive care; and Health education in hospital care: a tool to promote the autonomy of postpartum women. Final considerations: The findings indicated that hospital care for women in the postpartum period can be permeated by weaknesses related to biologicist care, and by potentialities based on the humanization of care. Furthermore, the importance of health education in hospital care can be seen, which can function as a potential tool aimed at promoting women's autonomy for self-care and child care. It is believed that this study may incite discussions to effect changes in the fields of work related to postpartum hospital care.